Case Report: A clinically relevant isolation of Gardnerella leopoldii guided by morphological and molecular evidence from a urinary tract infection case - Chen, Liangyou; Weng, Wei; Li, Dan; Xie, Weipeng; Lu, Lingling; Li, Shuo (Frontiers in Medicine, 2025)
BackgroundThe genus Gardnerella is commonly found in the vaginal ecosystem and is considered a covert pathogen of the urinary tract. However, Gardnerella vaginalis had been the only recognized species of the genus Gardnerella for decades. Cases regarding the clinical relevance of Gardnerella leopoldii have rarely been reported, which is crucial for fully understanding the various species within the genus Gardnerella.Case presentationA 72-year-old female patient was admitted to the hospital with gross hematuria and complaints of waist soreness. Physical examinations, including those of the head, chest, and abdomen, along with routine laboratory tests such as white blood cell (WBC) count and proportion, liver function, and renal function, yielded normal results. However, the patient also exhibited significantly elevated levels of serum C-reactive protein (CRP) and abnormal urinary test findings, which revealed positive results for occult blood and leukocyte esterase, and increased counts of erythrocyte and leukocyte. To further evaluate the urinary system, computerized tomography urography (CTU) was performed. The CTU results revealed multiple weakly enhanced foci in the right kidney and thickening of the right ureter, renal pelvis, calyces, and bladder walls. Based on the above findings, the initial diagnosis included hematuria, hydronephrosis, and urinary tract infection (UTI). To identify the causative pathogens, we employed a comprehensive approach that included microscopic morphology, Sanger sequencing, and metagenomic next-generation sequencing (mNGS). Finally, both Mycobacterium tuberculosis and G. leopoldii were identified as the co-infecting etiological agents responsible for the patient’s urinary tract infection.ConclusionThis case represents the first documented isolation of clinically relevant G. leopoldii, guided by morphological and molecular evidence from a clinical urine sample. It highlights the potential of mNGS as a promising tool for identifying previously unrecognized species and offers valuable insights to enhance the understanding of clinically relevant microorganisms.